Typification and taxonomic re-evaluation of Centaurea crnogorica and C. gjurasinii, two neglected yellow-flowered endemics of the Balkan Peninsula (Centaurea sect. Acrocentron, Asteraceae) - Novaković, Jelica; Mráz, Patrik; Stešević, Danijela; Marin, Petar D.; Zlatković, Bojan; Lakušić, Dmitar; Janaćković, Pedja (Phytotaxa, 2020)
In the most recent taxonomic literature, Centaurea crnogorica and C. gjurasinii, two neglected yellow-flowered taxa of C. sect. Acrocentron, have been treated as heterotypic synonyms of C. chrysolepis. Based on morphometric study, and study of type specimens and living plants from the locus classicus of C. gjurasinii and the only known population of C. crnogorica, as well as from several populations of C. chrysolepis from Eastern Serbia, we have found morphological differences among these three taxa. This has allowed us to re-evaluate taxonomic status of both, C. crnogorica and C. gjurasinii, which merit the species rank. The names C. crnogorica and C. gjurasinii are typified, and new expanded descriptions and illustrations are provided. We assessed also their conservation status. Because of their rarity, both taxa being narow endemics of two mountain ranges in Montenegro (the Durmitor Mts. and the Prokletje Mts.) and having small population sizes, C. crnogorica and C. gjurasinii are evaluated as critically endangered at national and global levels.